Dismissal informs the priorities of endometriosis patients in New Zealand - Ellis, Katherine; Munro, Deborah; Wood, Rachael (Frontiers in Medicine, 2023)
Introduction: Endometriosis is a common condition with average delays to diagnosis in New Zealand of almost nine years. Methods: Fifty endometriosis patients participated in anonymous, asynchronous, online group discussions about their priorities, and their experiences with the development of symptoms, seeking a diagnosis, and receiving appropriate treatment. Results: Higher subsidy of care was the top change endometriosis patients wanted, followed by more research funding. When asked to choose whether research should be focused on improving diagnosis and or improving treatment methods, the results were evenly split. Within this cohort, patients highlighted they did not know the difference between normal menstrual discomfort and pathological endometriotic pain. If, upon seeking help, medical practitioners classified their symptoms as “normal”, these dismissals could instill doubt in patients, which made it more difficult for them to continue to seek a diagnosis and effective treatments. Patients who did not express dismissal had a significantly shorter delay from symptom onset to diagnosis of 4.6 ± 3.4 years, versus 9.0 ± 5.2 years. Conclusions: Doubt is a frequent experience for endometriosis patients in New Zealand, which was reinforced by some medical practitioners who were dismissive of their pain and thus prolonged the patient’s delay to diagnosis.